PERANAN HOUSEKEEPING ATTENDANT DALAM PENYIAPAN KAMAR TAMUDI TONYS VILLAS RESORT SEMINYAK - Ida Ayu Putu Sulastri; Sriayuni, Anak Agung Ayu Erlina; Sunarprasetyo, mahardjono; Trianingrum, Ni Nyoman Nidya (Universitas Triatma Mulya, 2022)
The purpose of this study was to determine the role of the housekeeping attendant in preparing guest rooms at Tonys Villas Resort Seminyak, the obstacles faced by the housekeeping attendant in preparing guest rooms, and how to overcome these obstacles. This study uses quantitative and qualitative data types, obtained from primary data sources and secondary data. This study uses research instruments to improve research results by means of observation, interviews and documentation, as well as using formal and informal data presentation techniques that aim to explain the role of housekeeping attendant in preparing guest rooms at Tonys Villas Resort Seminyak. The results of the role of the housekeeping attendant in preparing guest rooms at Tonys Villas Resort Seminyak are: providing job training for employees at Tonys Villas Resort Seminyak, both in preparation for guest rooms, maintaining cleanliness, tidiness, beauty of guest rooms, cleanliness of employees, equipment, and area at Tonys Villas Resort Seminyak and maintain standard operating procedures for preparing guest rooms at Tonys Villas Resort Seminyak.